Species-specific variation in the phosphorus nutritional sources by microphytoplankton in a Mediterranean estuary - MARTINEZ SOTO, MARLY C.; Basterretxea, Gotzon; Garcés, Esther; Anglès, Silvia; Jordi, Antoni; Tovar-Sanchez, Antonio (Frontiers in Marine Science, 2015)
We investigated the species-specific phosphorus (P) nutrition sources in the microphytoplankton community in the Mahon estuary (Minorca, Western Mediterranean) in 2011, under two contrasting hydrographic scenarios. Estuarine flow, nutrient concentrations, phytoplankton community composition and enzyme-labeled fluorescence (ELF) were measured in June and October, corresponding to the beginning and the end of summer. Dissolved inorganic nitrogen (DIN) and inorganic phosphate (Pi) exhibited enhanced concentrations in the inner estuary where N:P molar ratios suggested P-limitation in both surveys. Pi was low and variable (0.09±0.02 μmol•l-1 in June and 0.06±0.02 μmol•l-1 in October), whereas organic phosphorus remained a more reliable P source. Even though ambient Pi concentrations were slightly higher on June, when the microphytoplankton assemblage was dominated by dinoflagellates, the percentage of cells expressing ELF labeling was notably higher (65% of total cells) than in October (12%), when the presence of diatoms characterized the microphytoplankton community. ELF was mainly expressed by dinoflagellate taxa, whereas diatoms only expressed significant AP in the inner estuary during the June survey. A P-addition bioassay in which response of AP to Pi enrichment was evaluated showed remarkable reduction in AP with increasing Pi. However, some dinoflagellate species maintained AP even when Pi was supplied in excess. We suggest that in the case of some dinoflagellate species AP is not as tightly controlled by ambient Pi as previously believed. AP activity in these species could indicate selective use of organic phosphorus, or slow metabolic response to changes in P forms, rather than physiological stress to low Pi availability. We emphasize the importance of identifying the links between the different P sources and the species-specific requirements, in order to understand the ecological response to anthropogenic biogeochemical perturbations.